Hey there!
Let's start by finding what 1% of 210 is.
This can be done by dividing 210 by 100, since 1% is the same as 1/100 of something.
210 ÷ 100 = 2.1
To find 36%, we can multiply 2.1 by 36.
2.1 x 36 = 75.6
So, 36% of 201 is 75.6.
Hope this helps!
120$. 100%
X$. 8.33%
X= 120• 8.33/100
X=9.99 $
The term that can be added to the list so the GCF is 12h3 would be 48h5.
The reason being is that 48 is first divisible by 12 and does not yield a fraction, and we can remove upon dividing 3 h's from this term as it contains a total of 5 h's.
Note the improper fraction. Change it into a mixed fraction
3/2 = 2/2 + 1/2
2/2 = 1
5 + 1 1/2
Simplify.
5 + 1 = 6
6 1/2 is your answer
hope this helps
Answer:
![(x^2 - 9)(x + 2)](https://tex.z-dn.net/?f=%20%28x%5E2%20-%209%29%28x%20%2B%202%29%20)
Step-by-step explanation:
Given:
![x^2 + 5x + 6](https://tex.z-dn.net/?f=%20x%5E2%20%2B%205x%20%2B%206%20)
![x^2 - x - 6](https://tex.z-dn.net/?f=%20x%5E2%20-%20x%20-%206%20)
Required:
LCM of the polynomials
SOLUTION:
Step 1: Factorise each polynomial
![x^2 + 3x + 2x + 6](https://tex.z-dn.net/?f=%20x%5E2%20%2B%203x%20%2B%202x%20%2B%206%20)
![(x^2 + 3x) + (2x + 6)](https://tex.z-dn.net/?f=%20%28x%5E2%20%2B%203x%29%20%2B%20%282x%20%2B%206%29%20)
![x(x + 3) + 2(x + 3)](https://tex.z-dn.net/?f=%20x%28x%20%2B%203%29%20%2B%202%28x%20%2B%203%29%20)
![(x + 2)(x + 3)](https://tex.z-dn.net/?f=%20%28x%20%2B%202%29%28x%20%2B%203%29%20)
![x^2 - x - 6](https://tex.z-dn.net/?f=%20x%5E2%20-%20x%20-%206%20)
![x^2 - 3x +2x - 6](https://tex.z-dn.net/?f=%20x%5E2%20-%203x%20%2B2x%20-%206%20)
![x(x - 3) + 2(x - 3)](https://tex.z-dn.net/?f=%20x%28x%20-%203%29%20%2B%202%28x%20-%203%29%20)
![(x + 2)(x - 3)](https://tex.z-dn.net/?f=%20%28x%20%2B%202%29%28x%20-%203%29%20)
Step 2: find the product of each factor that is common in both polynomials.
We have the following,
![x^2 - x - 6 = (x + 2)(x - 3)](https://tex.z-dn.net/?f=%20x%5E2%20-%20x%20-%206%20%3D%20%28x%20%2B%202%29%28x%20-%203%29%20)
The common factors would be: =>
(this is common in both polynomials, so we would take just one of them as a factor.
and,
![(x - 3)](https://tex.z-dn.net/?f=%20%28x%20-%203%29%20)
Their product = ![(x - 3)(x + 3)(x +2) = (x^2 - 9)(x + 2)](https://tex.z-dn.net/?f=%20%28x%20-%203%29%28x%20%2B%203%29%28x%20%2B2%29%20%3D%20%28x%5E2%20-%209%29%28x%20%2B%202%29%20)